Reigious Moderation in Caring for Indonesian Plurality (Analysis of Mental Revolution from The Qur’an Perspective) - Panji Ansari (Publication of the International Journal and Academic Research, 2024)
Indonesia is known as a diverse country with a variety of religions, ethnicities, cultures, customs, and languages. However, behind this gift, there are differences in views in responding to issues, especially regarding religious issues. Differences in views will later give rise to acts of intolerance, hatred, extremism, and radicalism, and ultimately lead to divisions between religious communities. Therefore, as an effort to maintain harmony between religious communities, religious moderation, and mental revolution are present as effective steps that will give birth to solutions for maintaining the diversity that exists in Indonesia. This research aims to find verses from the Qur'an about mental revolution and religious pluralism as well as solutions to religious moderation in mental revolution to address the phenomenon of religious pluralism. By using qualitative research methods and literature, findings were produced as solutions for maintaining diversity in Indonesia, namely (1) Aligning Pancasila with Qur'anic values; (2) Diversity must be managed well; (3) Religious Leaders must Set a Good Example (Socio-Institutional Approach); (4) Prioritizing a sense of protecting the nation and state; (5) Taking a Cultural Approach (Dialogue)